Results of screening for cervical cancer among pregnant and non-pregnant women in Brazil. Issue 1 (July 2015) - Xavier-Júnior, José C.C.; Vale, Diama B.; Vieira, Luiz F.F.; Lima, Marcelo T.; Zeferino, Luiz C.; Dufloth, Rozany M.
Abstract: Objective: To compare cervical cytology test results among pregnant and non-pregnant women, and to assess associations with age, screening history, and onset of sexual intercourse. Methods: A retrospective analysis was conducted of cervical smears obtained from women aged 18–34 years in the Campinas region of Brazil between January 2000 and December 2009. Eligible participants had not undergone cytological screening within the previous year and had no history of precursor lesions or cervical cancer. Multinomial logistic regression was performed for different age groups, with high-grade squamous intraepithelial lesions (HSILs) as the endpoint. Results: Overall, 3072 (0.4%) of 861 353 non-pregnant women and 135 (0.4%) of 37 568 pregnant women had HSILs. Odds of HSIL among pregnant and non-pregnant women did not differ in any age group. An increased age at first sexual intercourse among pregnant women reduced odds of HSILs in all age groups (odds ratio 0.9 [95% confidence interval 0.8–0.9] for all). Among women aged 21–24 years, 25–29 years, and 30–34 years, some associations were identified between an interval of less than 5 years since previous screening and reduced odds of HSILs. Conclusion: Mandatory cervical cytology screening does not seem to be necessary for pregnant women; protocols in place for non-pregnant women should be followed.